Ônus da prova na Ação Civil Pública ambiental sob a ótica do conflito de direitos fundamentais - Ferreira, Eduardo de Campos (2018)
This paper aims at reviewing potential conflicts involving the fundamental right of environmental integrity and the right for defense, including constitutional procedural guarantees related thereto, focusing on the burden of proof on environmental public civil actions. Taking into consideration majority of doctrine and judicial precedents as regards to burden of proof on environmental public civil actions, the purpose of this paper is to contribute for the importance of burden of proof on environmental judicial cases. This paper critically analyzes the way doctrine and case law are defending burden of proof inversion on environmental cases. As from the definition of fundamental rights theory that is best based on national legal system, it analyzes conflicts involving the environmental integrity as fundamental right; precautionary principle as broad justification for solving such conflicts; and conflicts involving right for defense and procedural guarantees deriving thereto. Assuming the importance of pieces of evidence for proper civil procedure, it examines proper manner for distribution of the burden of proof, criticizing the grounds currently alleged for inversion of the evidentiary burden. The conclusion is that the rule of proportionality is adequate to better identify cases wherein the dynamic distribution of the burden of proof in the environmental public civil actions, making sure that the fundamental right for defense will not be suppressed due to a generic purpose of facilitating protection of environmental right in judicial cases